Protection of Human Rights in the Legal Process Involving Celebrities in Indonesia: A Top Socio-Legal Study, The Trial by Media Phenomenon - M. Saeful Amri; Agus Irfan; Wahyu Aji Pratama (Universitas Amikom Purwokerto, 2025)
The phenomenon of celebrity involvement in legal proceedings in Indonesia often attracts massive public and media attention. This situation raises new issues related to human rights protection, particularly when the media shapes public opinion before the legal process is complete. The practice of trial by media can threaten the principles of presumption of innocence and due process of law, which are key pillars of the rule of law. This study aims to examine human rights protection in legal proceedings involving celebrities in Indonesia through a socio-legal approach. A juridical-normative approach is used to analyze constitutional provisions and laws related to the rights of suspects, press freedom, and procedural justice. Meanwhile, a sociological approach is used to understand the dynamics of media reporting, public opinion, and social judgment practices that occur digitally. The results show that media representations of celebrity cases often emphasize sensational aspects rather than legal substance, resulting in premature public perception of an individual's guilt or innocence. The resulting public pressure can then influence the decisions of law enforcement officials and the communication strategies of judicial institutions. Furthermore, celebrities, especially women, are more vulnerable to moral stigmatization and psychological vulnerability due to excessive public exposure. This research emphasizes the need to strengthen synergy between the judicial system, media oversight bodies, and the public to ensure comprehensive human rights protection. Reforming digital media ethics, improving legal literacy, and establishing reputation restoration mechanisms are crucial steps to ensure substantive justice is maintained in an era of open information.